Neighbors, neighbor-love, and our animal neighbors - Largen, Kristin Johnston (Word & world, 2017)
Defining the Christian duty to those around them as "neighbor-love", Kristin Johnston Largen understands this as the necessity of taking actions to work for those around us. She then suggests that this concept of "neighbor-love", with its imperative to action, must also be expanded to the animals with which we share the world, and who are suffering from exploitation.